Design of microstrip patch array antenna using LTCC technology for 5 GHz band applications / Nik Ruziana Nik Abdul Talib - Nik Abdul Talib, Nik Ruziana (2013)
The purpose of this project focuses on the design and analysis of rectangular planar array microstrip antenna with a non-contacting feed. The type of non-contacting feeding used is aperture coupled technique. The antenna concept is based on 5 GHz operating frequency using Low Temperature Cofired Ceramics (LTCC) technology. The antenna design composed of eight layer of substrates using Ferro A6S material with relative permittivity of 5.9.Microstrip patch of the array antenna are printed on the top of substrate which is at layer eight while the feed line is located on the bottom substrate of layer one. The proposed antenna design consist of three design of array antenna which is two, four and six patches of array antenna using aperture coupled feed with eight layer of substrate. The single patch microstrip antenna having eight layer of substrate using aperture coupled feed is also designed as a benchmark for designing those array antennas. All the design is using the same material of substrate which is Ferro A6S. The parameters of patch dimension is varies in order to achieved the desired operating frequency. The multilayer microstrip patch array antenna was designed and optimized using CST Microwave Studio Suite 2011 software. The simulation result were analyzed and presented in terms of return loss (S11 ), radiation pattern, gain, directivity, Voltage Standing Wave Ratio (VSWR) and bandwidth. The simulation result for every proposed design will be analyzed and discussed in details.